2015
DOI: 10.5539/ass.v11n10p153
|View full text |Cite
|
Sign up to set email alerts
|

International Student’s Academic Achievement: Contribution of Gender, Self-efficacy and Socio-cultural Adjustment

Abstract: International students who pursue their education in other country have to cope various challenges related to their adjustment. Successful adjustment to higher learning institution becomes an important issue, failure to which may hinder self-efficacy and their academic achievement. Aim of current research is to investigate the influence of self-efficacy, and socio-cultural adjustment on their academic achievement among International students in Malaysia. Two hundreds International students were randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…However, it found gender of an international student to be associated with academic problems. This finding is consistent with Wang's (2009) study, who found that gender is a significant predictor of international students' acculturation difficulty; and academic achievement (Khan, Hamdan, Ahmad & Mustaffa, 2015). In the views of Contreras-Aguirre and Gonzalez Y Gonzalez, (2017), female students' self esteem and low resilience could be responsible for why they face greater academic challenges, and general settlement issues.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, it found gender of an international student to be associated with academic problems. This finding is consistent with Wang's (2009) study, who found that gender is a significant predictor of international students' acculturation difficulty; and academic achievement (Khan, Hamdan, Ahmad & Mustaffa, 2015). In the views of Contreras-Aguirre and Gonzalez Y Gonzalez, (2017), female students' self esteem and low resilience could be responsible for why they face greater academic challenges, and general settlement issues.…”
Section: Discussionsupporting
confidence: 86%
“…There is a wealth of studies on the experiences of international students in foreign institutions, however, studies focusing mainly on Nigerian students' experiences have been modest. Such studies have explored Turkish students (Duru & Poyrazli, 2007); Asia, South America and Europe (Wang, 2009); Malaysia (Khan, Hamdan, Ahmad & Mustaffa, 2015); United states (Contreras-Aguirre & Gonzalez Y Gonzalez, 2017; Poyrazli & Grahame, 2007;Trice, 2004). Given the recent influx of Nigerian students to foreign institutions, it is of great importance to explore their experiences to guide future international students studying in the same or similar regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Culture is about a people's way of life, their heritage and language; pride and uniqueness as a people (Li & Ruan, 2015). Traditional ceremonies including weddings and commitment, funerals and memorials, baby naming and adoptions are often attended by all persons (Khan, et al, 2015). Each ceremony is personalized to reflect the needs, beliefs and values of the couple or family.…”
Section: Introductionmentioning
confidence: 99%
“…However, an inability to achieve such academic goals may create anxiety and sense of lacking self-confidence, and may also affect the funding which the learners receive from their families. Further, learners might lose their incentive towards study and motivation to study hard and spend more time in studying when they do not achieve their academic goals [40,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%